UPAYA PENINGKATAN HASIL BELAJAR KIMIA SISWA MELALUI MODEL DISCOVERY LEARNING PADA BAHAN TITRASI ASAM BASA - Diyani Wahyu Ningsih; Muchlis (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2023)
This study aims to determine the improvement of learning outcomes by applying the Discovery Learning (DL) model on acid-base titration material. This research was conducted on phase F students, especially in class XI chemistry 2 totaling 35 students. This research method is Classroom Action Research consisting of 2 cycles of each cycle 1 meeting. The results obtained in this study are the learning outcomes of students. In cycle I, the number of students who have reached the minimum completeness criteria is 15 students (42.8%). In cycle II, the number of students who had reached the minimum completeness criteria was 29 students (82.8%). There was an increase in the percentage of completeness from cycle I to cycle II by 40.0%.